Reducing compassion fatigue, secondary traumatic stress, and burnout : a trauma-sensitive workbook - Steele, William (New York, NY : Routledge, 2020)
"Reducing Compassion Fatigue, Secondary Traumatic Stress, and Burnout addresses the vital questions mental health providers have about self-care and its relationship to clinical practice. Packed with activities, worksheets, and interactive learning tools, the text provides neuro-based and trauma-sensitive recommendations for improving the ways clinicians care for themselves"--
OCLC-licensed vendor bibliographic record.
Keywords: Secondary traumatic stress; Burn out (Psychology); Job stress; Human services personnel -- Mental health; Mental health personnel -- Mental health; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health